PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BAGI SISWA KELAS III SDN PENGKOL 01 - Fani, Kiki Dwi; Pratiwi, Veronika Unun; Antana, Agus Sri (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to improve the learning outcomes of third-grade students in Pancasila Education at SDN Pengkol 01 through the implementation of the Problem-Based Learning (PBL) model. The research method used was Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, tests, and documentation. The results showed an improvement in students’ learning outcomes, with an average mastery increase of 65% in the first cycle and a significant rise to 85% in the second cycle. It can be concluded that the implementation of the Problem-Based Learning model effectively improved students’ learning outcomes in Pancasila Education, as evidenced by the increase in mastery level among third-grade students at SDN Pengkol 01.